STRATEGI PEMASARAN SMK CIPTA MANDIRI PAMIJAHAN DALAM PERSPEKTIF TEORI BAURAN PEMASARAN DAN MARKETING SYARIAH - Misno; Ash-Shidiqie, Hasbi; Soleh (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2022)
This research was conducted to determine the extent to which Marketing Mix Theory and Sharia Marketing play a role in the marketing carried out by SMK Cipta Mandiri. This research uses qualitative methods of phenomenology and normative legal studies, namely looking at the events that exist at SMK Cipta Mandiri in terms of marketing and analyzing the concept of marketing mix theory and its sharia perspective.The research results show that SMK Cipta Mandiri has implemented a marketing mix theory and in a sharia perspective in conducting marketing practices when looking for new student candidates such as Product, Price, Place, Promotion, Process, Physical Evidence and People and all of them have run according to sharia, which is prohibited. Commit fraud, take the rights of others vanity, and are not gharar